Sistem Informasi Kepegawaian pada PT Developer XYZ Menggunakan Metode RUP - Aditya Al Assad; Yulistia Yulistia (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
PT Developer XYZ is a company engaged in housing development and property construction services. The company faces several challenges in human resource (HR) management due to the use of manual systems, such as the accumulation of application files and the risk of attendance data manipulation. This research aims to design and develop a web-based HR information system using the Rational Unified Process (RUP) methodology with various features, including HR data management, digital recruitment, online leave requests, task management, and digital archiving. The system is built using web-based technology, with Express for the backend, React for the frontend, and MySQL as the database. The results of this research successfully implemented a system that reduces the time and resources required, enhances transparency, improves data accuracy, and facilitates easier access to HR-related documentation.